Carbon Cycling in the World's Deepest Blue Hole. Issue 2 (21st February 2020) - Yao, P.; Wang, X. C.; Bianchi, T. S.; Yang, Z. S.; Fu, L.; Zhang, X. H.; Chen, L.; Zhao, B.; Morrison, E. S.; Shields, M. R.; Liu, Y. N.; Bi, N. S.; et al.
Abstract: Blue holes are unique geomorphological features with steep biogeochemical gradients and distinctive microbial communities. Carbon cycling in blue holes, however, remains poorly understood. Here we describe potential mechanisms of dissolved carbon cycling in the world's deepest blue hole, the Yongle Blue Hole (YBH), which was recently discovered in the South China Sea. In the YBH, we found some of the lowest concentrations (e.g., 22 μM) and oldest ages (e.g., 6, 810 years before present) of dissolved organic carbon, as well as the highest concentrations (e.g., 3, 090 μM) and the oldest ages (e.g., 8, 270 years before present) of dissolved inorganic carbon observed in oceanic waters. Sharp gradients of dissolved oxygen, H2 S, and CH4 and changes in bacterially mediated sulfur cycling with depth indicated that sulfur‐ and/or methane‐based metabolisms are closely linked to carbon cycling in the YBH. Our results showed that the YBH is a unique and easily accessible natural laboratory for examining carbon cycling in anoxic systems, which has potential for understanding carbon dynamics in both paleo and modern oceans—particularly in the context of global change. Plain Language Summary: Here, we report for the first time concentrations and isotopic composition of dissolved organic carbon (DOC) and dissolved inorganic carbon (DIC) along with geomorphological and geochemical parameters in the Yongle Blue Hole (YBH), South China Sea, the world's deepest blue hole. We found some of the lowest concentrations of DOC and the highest concentrations of DIC observed in coastal waters, that were both very old (their 14 C ages are 6, 810 and 8, 270 years, respectively). Such low DOC concentrations have not been observed in relatively shallow oceanic environments. DIC in surface waters of the YBH is mainly controlled by air‐sea exchange, which only impacts the upper 80 m. The decomposition of organic carbon and the sulfidic acid dissolution of carbonates in the YBH enhance the production of DIC in deep waters of the YBH. The profiles of physical, chemical, and microbial parameters in the YBH provide a natural laboratory for examining carbon cycling and other redox‐sensitive elements. Understanding the key mechanisms of biogeochemical pathways in anoxic systems is critical in our understanding of carbon cycling in both paleo and modern oceans. Key Points: Concentrations and isotopic composition of dissolved carbon in the world's deepest blue hole were examined for the first time Lowest concentrations of DOC and highest concentrations of DIC in oceanic waters were observed, and both were radiocarbon depleted Carbon cycling in the Yongle blue hole is unique from those of the open ocean